DIVERSITY AND DISTRIBUTION OF MACROALGAE AT SEKOTONG, WEST LOMBOK - ., Sukiman; Muspiah, Aida; Puji Astuti, Sri; Ahyadi, Hilman; Aryanti, Evy (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
Research to determine species diversity, classification and identification of key species and the distribution of macroalgae in coastal waters Sekotong, West Lombok has been done. The study was conducted by survey method, specimen collection and identification. Survey and sampling carried out in five locations in the waters of Sekotong: West Sekotong, Gili Nanggu, Gili Sudak, Gili Gede, and Bangko-Bangko. Based on the results of the inventory and identification is known that in the waters of Sekotong there are 61 species of macroalgae. Rhodophyta is the largest division with the highest species diversity, while Phaeophyta has the lowest number of species. Rhodophyta consists of 25 species, 17 genera and 11 families. Chlorophyta consists of 21 species, 11 genera and10 families. Phaeophyta consists of 15 species, 7 genera and 4 families. Key to the identification of species of macroalgae in Sekotong has been prepared based on morphologic characters. There are differences in the composition and species richness in the five beaches that have been surveyed. West Sekotong beach is area with the highest diversity of macroalgae at Sekotong, while the lowest diversity was found in the waters of Gili Nanggu